The Suckling Rat as a Model for Immunonutrition Studies in Early Life - Francisco J. Pérez-Cano; Àngels Franch; Cristina Castellote; Margarida Castell (Clinical and Developmental Immunology)
Diet plays a crucial role in maintaining optimal immune function. Research demonstrates the immunomodulatory properties and mechanisms of particular nutrients; however, these aspects are studied less in early life, when diet may exert an important role in the immune development of the neonate. Besides the limited data from epidemiological and human interventional trials in early life, animal models hold the key to increase the current knowledge about this interaction in this particular period. This paper reports the potential of the suckling rat as a model for immunonutrition studies in early life. In particular, it describes the main changes in the systemic and mucosal immune system development during rat suckling and allows some of these elements to be established as target biomarkers for studying the influence of particular nutrients. Different approaches to evaluate these immune effects, including the manipulation of the maternal diet during gestation and/or lactation or feeding the nutrient directly to the pups, are also described in detail. In summary, this paper provides investigators with useful tools for better designing experimental approaches focused on nutrition in early life for programming and immune development by using the suckling rat as a model.